Multivariate regimeswitching GARCH with an application to international stock markets - Markus Haas; Stefan Mittnik (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
We develop a multivariate generalization of the Markov-switching GARCH model introduced by Haas, Mittnik, and Paolella (2004b) and derive its fourth-moment structure. An application to international stock markets illustrates the relevance of accounting for volatility regimes from both a statistical and economic perspective, including out-of-sample portfolio selection and computation of Value-at-Risk.
urn:nbn:de:hebis:30-53250
Keywords: C32; C51; G10; G11; 330; Conditional Volatility; Markov-Switching; Multivariate GARCH; ARCH-Modell; Multivariate Analyse; Markovscher Prozess; Volatilität; Theorie; Schätzung; Kapitalertrag; Börsenkurs; Value at Risk; USA; Deutschland; Großbritannien